9C.05: META-ANALYSIS OF AMLODIPINE VERSUS ANGIOTENSIN RECEPTOR BLOCKERS ON BLOOD PRESSURE, SOME ECHOCARDIOGRAPHIC INDICATORS OF LEFT VENTRICULAR DAMAGE AND ADVERSE EVENTS IN PATIENTS WITH HYPERTENSION. (June 2015) - Xu, H.; Wang, Q.; Yang, M.; Yu, J.
Abstract : Objective: The aim of this meta-analysis is to evaluate two echocardiographic indicators of left ventricular damage, amlodipine and angiotensin receptor blockers, and associated adverse events in patients with hypertension. Design and method: A meta-analysis was conducted using PubMed, Cochrane Library and EMBASE to investigate and analyze the effects of amlodipine versus angiotensin receptor blockers for blood pressure, associated adverse events, and cardiac structure and function. Data was collected from database inception through October 2014. Results: Nineteen randomized-control clinical trials were included in the meta-analysis. 4, 248 subjects from the collected trials were given either amlodipine or angiotensin receptor blockers (ARBs) for management of hypertension. The results showed no significant differences between amlodipine and ARBs in ability to lower blood pressure. However, when measuring the decrease of left ventricular mass index (LVMI), amlodipine was shown to be inferior to both irbesartan (weighted mean difference= -15.1, 95% confidence intervals: -22.97 to -7.23, P < 0.001) and valsartan (weighted mean difference = -17.77, 95% confidence intervals:-31.28 to -4.27, P = 0.01). Amlodipine showed decreased performance compared to losartan in early diastolic mitral annular velocity (E[Combining Acute Accent]), the ratio of left ventricular early diastolic filling velocity to early diastolic mitral annular velocity (E/E[Combining Acute Accent]) and an increased number of adverse events[(E[Combining Acute Accent]:weighted mean difference= -0.09, 95%CI -1.76 to -0.04, P = 0.04), (E/E[Combining Acute Accent]:weighted mean difference = 3.00, 95%CI 1.22 to 4.78, P = 0.001), (adverse events: OR = 3.78, 95%CI 1.29 to 11.06, P = 0.02)]. Additionally, amlodipine led to more adverse events when compared with valsartan (OR = 1.80, 95% confidence intervals:1.17 to 2.78, P = 0.008). Conclusions: Amlodipine is comparable to several ARBs in its potential to lower blood pressure. However, it is less effective in prevention of left ventricular hypertrophy and exhibits a higher incidence of clinically adverse events, such as dizziness, fatigue, headache, peripheral edema, and erectile dysfunction.